Qualidade física de um latossolo vermelho férrico sob sistemas de uso e manejo - Carvalho Filho, Alberto; Cirilo Carvalho, Luis Carlos; Centurion, Jose Frederico [UNESP]; Beutler, Amauri Nelson; Cortez, Jorge Wilson; Ribon, Adriana Aparecida (Universidade Federal de Uberlândia (UFU), 2009)
The soil physical quality is defined as the soil capacity to maintain the sustainable productivity during the years. To assess soil physical quality, attributes were evaluated in the layers of 0.0-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.40 m in acrustox. The experimental design was entirely randomized, with four systems of use ( corn, sugar-cane, pasture and native vegetation), four soil depths and four replications. The parameter evaluated were: texture, degree of clay flocculation, soil bulk density, porosity, water retention and "S" parameter. The usage and management systems caused soil physical degradation, being greater in pasture system with intensive usage, with smaller soil physical quality for plants development. The soil physical quality, evaluated by physical attributes, followed the following order: native vegetation > maize > sugar-cane > pasture. The Oxisol, although shows present excellent physical structure and needs an adequate management to prevent excessive compaction.

A qualidade física do solo é definida como a capacidade do solo manter a produtividade sustentável ao longo dos anos. Para mensurar a qualidade física foram avaliados atributos nas camadas de 0,0-0,10; 0,10-0,20; 0,20-0,30; 0,30-0,40 m em Latossolo Vermelho acriférrico, muito argiloso. O delineamento experimental foi inteiramente casualizado com quatro sistemas de uso (milho, cana-de-açúcar, pastagem e cerrado nativo), quatro profundidades e quatro repetições. Foram avaliadas as propriedades a seguir: composição granulométrica, grau de floculação das argilas, densidade e porosidade do solo, retenção de água e o parâmetro “S. Os sistemas de uso e manejo causaram degradação física do solo, destacando-se o sistema de uso com pastagem e pastejo intensivo com menor qualidade física do solo para o desenvolvimento das plantas. A qualidade física do solo, avaliada por meio dos atributos físicos, seguiu a seguinte ordem: cerrado > milho > cana-de-açúcar > pastagem. O Latossolo Vermelho acriférrico, apesar de apresentar excelente estrutura física, necessita de um manejo adequado para evitar a compactação excessiva.
Physical quality of an acrustox under usage systems
Keywords: porosity; Soil water content; Parameter "S"